2003
DOI: 10.1038/sj.onc.1206894
|View full text |Cite
|
Sign up to set email alerts
|

siRNA targeting of the viral E6 oncogene efficiently kills human papillomavirus-positive cancer cells

Abstract: The targeted inhibition of antiapoptotic factors in tumour cells may provide a rational approach towards the development of novel anticancer therapies. Using human papillomavirus (HPV)-transformed cells as a model system, we investigated if RNA interference (RNAi)-mediated gene silencing can be employed in order to overcome the apoptosis resistance of cancer cells. We found that both vector-borne and synthetic small interfering (si)RNAs, specifically directed against the antiapoptotic HPV E6 oncogene, restored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
283
4
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 303 publications
(305 citation statements)
references
References 44 publications
14
283
4
4
Order By: Relevance
“…These differences may be due to the different experimental setups. Whereas, we specifically target endogenous E6 by RNAi (Butz et al, 2003), the cited studies involved expression of the bovine papillomavirus (BPV) E2 protein (in order to block endogenous HPV18 E6 and E7 expression in HeLa cells) in combination with retrovirally re-expressed HPV16 E7. Both the ectopic expression of two heterologous viral proteins as well as the fact that the multifunctional BPV E2 can modulate apoptosis in HeLa cells via p53-independent mechanisms (Desaintes et al, 1999) may complicate this system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These differences may be due to the different experimental setups. Whereas, we specifically target endogenous E6 by RNAi (Butz et al, 2003), the cited studies involved expression of the bovine papillomavirus (BPV) E2 protein (in order to block endogenous HPV18 E6 and E7 expression in HeLa cells) in combination with retrovirally re-expressed HPV16 E7. Both the ectopic expression of two heterologous viral proteins as well as the fact that the multifunctional BPV E2 can modulate apoptosis in HeLa cells via p53-independent mechanisms (Desaintes et al, 1999) may complicate this system.…”
Section: Discussionmentioning
confidence: 99%
“…However, possible proapoptotic effects of IP10 that are HPV-independent were not investigated. In contrast, by the RNAi approach chosen in the present work, we target the E6 gene with high specificity (Butz et al, 2003) and the apoptotic effects are selectively observed in HPV-positive cells only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations